PENGARUH DUKUNGAN ORANG TUA TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA KELAS III SD AL-JIHAD - Santi Ekawati; Alfiah Junyani Arsyad; Sulis Handayani; Mutmainnah Ismayanti; Oki Sandra Agnesa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the effect of parental support on mathematics learning achievement of third-grade students at SD Al-Jihad Sorong. The background of this research is the phenomenon of varying levels of parental involvement in supporting children’s learning activities, particularly in the subject of mathematics which is often perceived as difficult. This study uses a quantitative approach with a correlational method. The population consisted of 60 third-grade students at SD Al-Jihad Sorong, with a sample of 52 students selected using purposive sampling technique. Data were collected using a parental support questionnaire and documentation of students’ mathematics report card scores. Data analysis employed simple linear regression and Pearson product-moment correlation techniques. The results showed that parental support had a significant positive effect on students’ mathematics learning achievement, with a correlation coefficient of r = 0.672 and a coefficient of determination of R² = 0.452, meaning that 45.2% of the variance in mathematics learning achievement was explained by parental support. The regression equation obtained was Ŷ = 32.14 + 0.58X. It is concluded that the higher the parental support provided to students, the better their mathematics learning achievement. These findings recommend that schools actively involve parents through educational programs to strengthen the role of the family in supporting children’s academic development.